Writing Nowa Huta : a cultural study of identity - Misteravich-Carroll, Natalie (2016)
This dissertation is a cultural-literary study of the Polish city Nowa Huta built in 1949 and commonly known as Poland's first "Socialist City." Slated to become a bastion of socialism, the initial purpose of the Steelworks and adjacent city was threefold: to stimulate Stalinist industrialization, to create a worker's paradise, and to act as an ideological symbol for Polish citizens. Above all else, Nowa Huta would prove that communist ideology could materialize a real, lived socialist utopia. As the grandest endeavor of the Six-Year Plan in Poland, Nowa Huta required an equally grand identity which was constructed by authors, filmmakers and artists guided by the official doctrine of socialist realism. Perceived as both a welcome opportunity for social and economic advancement and as a detested symbol of Stalinist hubris, Nowa Huta's contemporary identity remains locked in this lingering dichotomy. The goal of this dissertation is to examine the lasting influence of the Stalinist identity of Nowa Huta and to analyze how that original identity has informed subsequent texts, public perception, and the process of contemporary identity reconfiguration. Drawing on cultural theory, especially Raymond Williams' discussion of hegemony, this dissertation presents a chronological analysis of texts composed between 1949 and 2014 in their historical, political, and cultural framework. Narratives regarding Nowa Huta have evolved diachronically and parallel to historical events in Poland. Yet attempts to produce a new identity, especially in the post-1989 period, consistently engage with Stalinist era discourse. This study examines how the myths, narratives, and symbols of the Stalinist identity of Nowa Huta are continuously negotiated in the evolution of Nowa Huta's identity. By focusing on the intertextual strategies of appropriation and resignification, this dissertation examines the causative power of texts and their ability to create, manipulate, or denigrate the identity of a city and its people